Did Massachusetts Health Reform Affect Veterans Affairs Primary Care Use?. (February 2018) - Wong, Edwin S.; Maciejewski, Matthew L.; Hebert, Paul L.; Batten, Adam; Nelson, Karin M.; Fihn, Stephan D.; Liu, Chuan-Fen
Massachusetts Health Reform (MHR), implemented in 2006, introduced new health insurance options that may have prompted some veterans already enrolled in the Veterans Affairs Healthcare System (VA) to reduce their reliance on VA health services. This study examined whether MHR was associated with changes in VA primary care (PC) use. Using VA administrative data, we identified 147, 836 veterans residing in Massachusetts and neighboring New England (NE) states from October 2004 to September 2008. We applied difference-in-difference methods to compare pre–post changes in PC use among Massachusetts and other NE veterans. Among veterans not enrolled in Medicare, VA PC use was not significantly different following MHR for Massachusetts veterans relative to other NE veterans. Among VA–Medicare dual enrollees, MHR was associated with an increase of 24.5 PC visits per 1, 000 veterans per quarter ( p = .048). Despite new non-VA health options through MHR, VA enrollees continued to rely on VA PC.